Comparison of Unfavorable Outcome with and without Persistent Hyperglycemia in Patients with Acute Ischemic Stroke - Safdar Hussain Arain, Abdul Ghafoor Magsi, Fahim Ahmed Soomro, Muhammad Munwar Ali, Ali Hyder Mugheri, Abrar Shaikh, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the unfavorable outcome with and without persistent hyperglycemia in patients presenting with acute ischemic stroke. Study Design: Prospective observational study Place and duration of study: Department of Neurology, Chandka Medical College/Shaheed Mohtarma Benazir Bhutto Medical University, Larkana from 1st January 2021 to 30th September 2021. Methodology: Seventy ischemic stroke patients within the age group of 50-70 years were enrolled. There radiological imaging, clinical characteristics as well as sugar blood analysis was continuously monitored. The patients were divided into Group I and Group II (both having 35 patients each). Group I were those ischemic stroke patients with persistent hyperglycemia while Group II were those ischemic stroke patients who had no hyperglycemia. A comparison of primary and secondary outcomes of both groups was made and entered in a well structured questionnaire. Results: There was no significant variance among males and females of both groups. the mean rank of group I of ischemia and duration of hospitalization was much higher than group II. A significantly higher number of patients (74.2%) in group I with uncontrolled hyperglycemia lost their lives. The mechanical ventilation (82.8% vs 31.4%), vasopressin (85.7%vs 34.2%) and hemorrhagic transformation (31.4%vs 8.5%) was significantly higher in group I than group II respectively. Conclusion: There is a significant risk of unfavorable outcome in ischemic stroke patient with persistent hyperglycemia including a higher risk of mortality and mechanical ventilation requirement.